2017
DOI: 10.1001/jama.2016.19975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Glucose Monitoring on Glycemic Control in Adults With Type 1 Diabetes Using Insulin Injections

Abstract: IMPORTANCEPrevious clinical trials showing the benefit of continuous glucose monitoring (CGM) in the management of type 1 diabetes predominantly have included adults using insulin pumps, even though the majority of adults with type 1 diabetes administer insulin by injection.OBJECTIVE To determine the effectiveness of CGM in adults with type 1 diabetes treated with insulin injections.DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial conducted between October 2014 and May 2016 at 24 endocrinology pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
741
5
25

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 926 publications
(842 citation statements)
references
References 24 publications
34
741
5
25
Order By: Relevance
“…Despite technical problems with early generations of the technology, numerous studies have found that sustained use of CGM technology improved overall glycemic control in both adults and children with type 1 diabetes. 2,[4][5][6] Compared with intermittent episodic capillary fingerstick blood glucose testing, continuous glucose monitoring systems produce very large amounts of data. The development of automated data visualization tools for continuous glucose monitoring systems has been a major focus of research in academia and in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Despite technical problems with early generations of the technology, numerous studies have found that sustained use of CGM technology improved overall glycemic control in both adults and children with type 1 diabetes. 2,[4][5][6] Compared with intermittent episodic capillary fingerstick blood glucose testing, continuous glucose monitoring systems produce very large amounts of data. The development of automated data visualization tools for continuous glucose monitoring systems has been a major focus of research in academia and in industry.…”
Section: Introductionmentioning
confidence: 99%
“…A CGM device records blood glucose levels every 5 minutes and obtains glucose parameters, and patients are accordingly able to receive intensive glucose management 14. The aim of this study was to clarify the detailed dynamics of blood glucose levels in acute stroke patients regardless of the presence of diabetes mellitus using a CGM device and to identify the parameters related to death or dependency at 3 months and early neurological deterioration within 7 days after stroke.…”
mentioning
confidence: 99%
“…The mean HbA1c dropped in both groups to -1.0% in the CGM group and -0.4% in the SMBG group for an adjusted treatment-group difference of -0.6% (95% CI -0.8 to -0.3; P < 0.001). 42 The time spent in hypoglycemia (<70 mg/dL) was 43 min/day versus 80 min/day in the CGM versus SMBG groups, respectively, P = 0.002. 42 The GOLD trial used a crossover design with half of the 161 randomized participants using CGM for 6 months in addition to SMBG, followed by a 4-month washout period, then 6 months of usual care with SMBG alone, whereas the other half of the participants performed SMBG for the initial 6 months, and washout period followed by 6 months of CGM.…”
Section: Impact Of Cgm On Hypoglycemia and Hypoglycemia Unawarenessmentioning
confidence: 88%
“…42 The time spent in hypoglycemia (<70 mg/dL) was 43 min/day versus 80 min/day in the CGM versus SMBG groups, respectively, P = 0.002. 42 The GOLD trial used a crossover design with half of the 161 randomized participants using CGM for 6 months in addition to SMBG, followed by a 4-month washout period, then 6 months of usual care with SMBG alone, whereas the other half of the participants performed SMBG for the initial 6 months, and washout period followed by 6 months of CGM. 43 Followup data were available for 142 participants, who wore the CGM between 86.5% and 91.9% of the time assigned.…”
Section: Impact Of Cgm On Hypoglycemia and Hypoglycemia Unawarenessmentioning
confidence: 88%
See 1 more Smart Citation